ANALISIS BEBAN KERJA PADA PROSES PENGEPRASAN TANAMAN TEBU (SACCHARUM OFFICINARUM L.) LAHAN KERING DENGAN MENGGUNAKAN TRAKTOR TANGAN - Andriani Lubis; Syafriandi Syafriandi; Tinton Tonika (Universitas Andalas, 2015)
Indonesia started to apply and develop agricultural mechanization to increase agricultural productivity. However, the development of agricultural mechanization is not always get success, we still can found fatigue in operation of tool of agricultural mechanization , which if this still happen would able to make a decline of productivity. This research aims to find out of workload that produced by operator in stubble shaving process by using hand tractor with two different hand tractor engine rotation speeds, it is 1600 RPM and 1800 RPM. This research is located in sugarcane plantation at Kebun Tanjung Jatti, Binjai, Sumatera Utara.Key words: Ergonomic, Stubble Shaving, Sugarcane,Workload